PENGEMBANGAN INSTRUMEN ASESMEN AUTENTIK DALAM PEMBELAJARAN SEJARAH UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Fahruddin, Fahruddin; Darsono, Darsono (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2025)
This study aims to measure the effectiveness of implementing authentic assessment in history learning to enhance the critical thinking skills of high school students. The developed authentic assessment focuses on evaluating students' skills in analysis, evaluation, and synthesis of historical events. The method used is quantitative research with a quasi-experimental design, involving 200 students from SMAN 1 Yogyakarta and SMAN 5 Yogyakarta. The instruments used were written tests and questionnaires to measure the validity, reliability, and effectiveness of the assessment. Data were analyzed using content validity, construct validity, reliability, paired t-test, and gain score. The results showed that content validity increased from 0.85 to 0.90, and construct validity rose from 0.82 to 0.87. Reliability improved from 0.89 to 0.92, indicating high consistency in the instrument. The paired t-test results indicated a significant difference between the pre-test and post-test, with the t-value increasing from 2.8 to 5.4 (p < 0.05), while the gain score increased from 30% to 45%. These results show that authentic assessment is effective in improving students' critical thinking skills. This research contributes to the development of authentic assessment instruments and provides practical guidance for teachers to implement more contextual and in-depth evaluations.